Inoculação com Rhizobium tropici e adubação foliar com molibdênio na cultura do feijoeiro comum - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The common bean, in symbiosis with Rizobacteria Rhizobium tropici, is able to have its nitrogen exigence (N) satisfied with a biological fixation of nitrogen (BFN). Therefore, BFN is affected by molybdenum deficiency (Mo), since this nutrient is part of nitrogenase enzyme, responsible for the process. The aim of this work was to evaluate the common bean answer and their components: chlorophyll proportion, grain yield, number of husks by plant, number of grains by husk, weigh of one thousand seeds, fresh matter of the aerial part (FMAP) , dry matter of the aerial part (MDAP), roots fresh matter (FRM), dry roots matter (DRM), and biomass production of the cultivation to the use of seeds inoculation combined with the application of different doses of molybdenum (Mo) via foliar. The experiment was conducted in the 2nd crop, January to April 2015 in a Dysthrofic RED OXISOL, with average texture, in an experimental area irrigated by central pivot, in Urutai-Go. The experiment was led in randomized blocks, arranged in factorial scheme 2x4, with three replicates. The first factor corresponds to the inoculation or not of the rizobacteria race Rizobuim tropici, and the second factor, the doses of Molybdenum applied via foliar (0, 50, 100 and 150g ha–1). Seeds inoculation associated to the dose of 150 g ha-1 promoted significant increases in the development components and Grain yield of the common bean.
Keywords: Phaseolus vulgaris L.; Fixação biológica do nitrogênio; teor de nitrogênio; produtividade; Phaseolus vulgaris L.; Biological fixation of nitrogen; proportion of nitrogen; Grain yield; CIENCIAS AGRARIAS